2009
DOI: 10.1080/03014460902960263
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin polymorphism and diabetic nephropathy in Brazilian diabetic patients

Abstract: Diabetic nephropathy (DN) has an important impact on morbidity/mortality in diabetic patients. Genetic factors are probably involved in the development of this microvascular complication. Haptoglobin (Hp) is a genetically polymorphic glycoprotein that forms stable complexes with plasma-free hemoglobin (Hb) providing protection against heme-induced oxidative stress and kidney damage. The aim of the present study was to investigate the existence of association between the Hp genotypes and the presence of DN in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Studies of Israeli, Irish and Egyptian subjects [7,9,10] indicated that the Hp2-2 genotype may confer susceptibility to diabetic nephropathy. However, there was no association between Hp genotype and diabetic nephropathy in studies of Japanese, North American and Brazilian subjects [11,12,13]. These contradictory results may be due to differences in the distribution of Hp alleles in different populations, linkage disequilibrium near the Hp locus [11] or study design and sample size, as well as baseline characteristics of enrolled patients.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies of Israeli, Irish and Egyptian subjects [7,9,10] indicated that the Hp2-2 genotype may confer susceptibility to diabetic nephropathy. However, there was no association between Hp genotype and diabetic nephropathy in studies of Japanese, North American and Brazilian subjects [11,12,13]. These contradictory results may be due to differences in the distribution of Hp alleles in different populations, linkage disequilibrium near the Hp locus [11] or study design and sample size, as well as baseline characteristics of enrolled patients.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies of Hp have investigated its impact on diabetic nephropathy [7,9,10,11,12,13], one of the common precursors to CKD; however, the relationship varies among different ethnic populations. Studies of Israeli, Irish and Egyptian subjects [7,9,10] indicated that the Hp2-2 genotype may confer susceptibility to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity was defined as body mass index (BMI) 30 kg/m 2 28 . Diabetic retinopathy (DR) and diabetic nephropathy (DN) had been previously investigated in these patients 21,29 . Serum creatinine was measured by a modified Jaffé method, and the reference values for males and females were ≤1.20 mg/dL and ≤0.90 mg/dL, respectively 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Ceruloplasmin that was synthesized primarily in the liver was accepted as an acute phase protein that shows a moderate response to conditions such as inflammation and tissue damage; as well as an antioxidant (Güngör et al, 2004). Haptoglobulin (Hp) induction provides protection against oxidative stress and kidney damage, creates a stable complex with free plasma hemoglobin, and is a genetic polyphormic glycoprotein (Wobeto et al, 2009;Blum et al, 2010). Plasma haptoglobin increases in acute infections, trauma, and nephrotic syndrome.…”
Section: Resultsmentioning
confidence: 99%